Antimicrobial Efficacy of a Portable UV-C-Based Coating Activation Device against Candida albicans Biofilm and SARS-CoV-2 as an Additional Feature: An In Vitro Study - Adityakrisna Yoshi Putra Wigianto; Megumi Watanabe; Yuki Iwawaki; Takaharu Goto; Tamaki Otsuki; Tetsuo Ichikawa (Hygiene, 2024)
This in vitro study aimed to confirm the effect of the additional features of Kirei Keep Light (KKL), a commercial UV-C irradiation system that was originally created for coating the surface of removable dentures with photoreactive 2-methacryloyloxyethyl phosphorylcholine (MPC), on the antimicrobial efficacy aspect against Candida albicans biofilm on a denture base material (PMMA) and SARS-CoV-2. Materials and Methods: The antimicrobial efficacy on C. albicans biofilm was evaluated through quantitative (CFU) and qualitative (SEM images) analysis of three groups: no treatment (control), KKL, and immersion in a disinfectant solution, MCAE. The quantitative evaluation on SARS-CoV-2 was performed by comparing the untreated (control) group and the KKL group. Results: In comparison with the control group (2.39 × 106 CFU/mL), KKL irradiation resulted in a 91.01% reduction in C. albicans biofilm (2.15 × 105 CFU/mL), whereas for the MCAE group, this reduction was 99.98% (4.64 × 102 CFU/mL). The SEM image results also corroborate the CFU results, which showed that the fewest clean surfaces were found in the control, and this gradually increased with KKL and MCAE. SARS-CoV-2 inhibition, indicated by its TCID50 value, demonstrated that KKL almost completely inhibited SARS-CoV-2 infection and replication (99.99% reduction). Conclusion: KKL possesses antimicrobial efficacy on C. albicans biofilm on PMMA and SARS-CoV-2.